Exploring English communication needs in the heavy equipment industry: Insights from industry practitioners - Elisa Ratih; Dita Lupita Sari (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
The heavy equipment industry requires employees to possessnot only technical expertise but also adequate Englishcommunication skills to interact effectively in multinationalworkplaces. This study aims to explore the Englishcommunication needs of professionals in the heavy equipmentsector as a basis for designing an industry-oriented Englishcurriculum. Data were collected through semi-structuredinterviews with industry practitioners from leading heavyequipment companies in Indonesia. The findings reveal thatEnglish is primarily used in technical documentation, safetycommunication, and daily interaction with expatriates, withwriting and speaking skills being the most crucial. Furthermore,specific vocabulary related to machinery operation,troubleshooting, and safety procedures emerged as essentialfor workplace communication. The results suggest that anEnglish curriculum for heavy equipment engineering programsshould integrate task-based activities, workplace simulation,and multimodal strategies to bridge the gap betweenacademic instruction and industry demands. This studyprovides valuable insights for curriculum developers, vocationaleducators, and policymakers in aligning English teaching withnational human capital development goals.